Globalization and the Transformation of the English Novel (NPRC Journal of Multidisciplinary Research, 2026)
Background: Globalization has significantly transformed literary production and circulation, particularly influencing the English novel’s thematic scope, formal experimentation, and global readership. Despite extensive critical discussion, existing scholarship often remains fragmented across theoretical traditions.Methods: This study adopts a qualitative, interpretive approach based exclusively on secondary sources. A systematic review and thematic analysis of peer reviewed books, journal articles, and authoritative literary criticism were conducted using theoretical frameworks from world literature, postcolonial studies, Marxist cultural theory, and globalization studies.Results: The analysis demonstrates that globalization has reshaped the English novel through the increased prominence of transnational themes such as migration, displacement, cultural hybridity, and economic precarity. Formally, contemporary novels employ fragmented narratives, multiple perspectives, and multilingual strategies to reflect global mobility and cultural complexity. The study also reveals how global publishing markets, literary prizes, and international readerships influence literary visibility while reproducing inequalities in recognition and access.Conclusion: The English novel emerges as a dynamic and adaptable literary form capable of mediating between local experiences and global processes. However, its global circulation remains shaped by uneven power relations rooted in historical and economic structures.Novelty: This study contributes an original conceptual synthesis by integrating world literature, postcolonial, and political-economic perspectives into a unified analytical framework, demonstrating how thematic transformation, narrative form, and global literary markets jointly shape the contemporary English novel, an approach rarely articulated within a single, methodologically explicit study.